The Right to Play versus Early Professionalisation: A Children’s Rights Perspective on Youth Sport - Garayova, Lilla (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This paper adopts a children’s rights perspective to examine the tension between children's right to play and the growing trend of early professionalisation in youth sport. It traces the evolution of the right to play in international law and documents how intensive training regimes and early specialization can compromise children’s health, education, and rest. The analysis highlights how commercialized youth sports environments often infringe upon multiple child rights and conflict with the best interests of the child. The paper proposes a child rights–based framework for youth sport governance that balances the right to play with early professionalisation in sports. The analysis situates early professionalisation within the normative framework of the United Nations Convention on the Rights of the Child, with particular attention to Article 31 – the right to play. This approach places youth sport into a legal accountability framework, which requires these practices to be assessed against binding child rights standards.